Kualitas Fisik Pakan Fermentasi Berbasis Limbah Sayur yang Disuplementasi dengan Limbah Tepung Ikan dalam Persentase yang Berbeda - Andi Sukma Indah; Siti Nuraliah (Jurnal Galung Tropika, 2025)
Vegetable waste has the potential to be animal feed, which is optimally utilized if fermented first. Vegetable waste is a source of fiber, and when fermented with fish meal waste, it can increase its nutritional quality. This study aimed to determine the physical quality of fermented vegetable waste supplemented with fish meal waste with different percentages. The study used a completely randomized design (CRD) consisting of four treatments and four replications. The treatments were the percentage of fish meal waste supplementation of 0, 5, 10, and 15%. The parameters observed were the pH value and organoleptic of fermented vegetable waste, including aroma, texture, color, and the presence of fungi. The results showed that fermented waste feed with different fish meal supplementation had a significant effect (P <0.05) on the variables, color, and aroma of fermented vegetable waste and had no significant effect (P>0.05) on the variables of pH value, texture, and the presence of fungi. Supplementation of 10% fish meal waste has a yellowish-green color and a solid texture and does not show the presence of fungi. Supplementation of 10% fish meal waste has a pH value of around 4.3 and shows a distinctive aroma of fermented products. Based on the study's results, fermented vegetable waste feed with 10% fish meal waste supplementation showed the best physical quality, including pH value, texture, color, aroma, and the presence of fungi.